2017
DOI: 10.1136/bcr-2017-221204
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of ventricular septal perforation following percutaneous coronary intervention for acute myocardial infarction

Abstract: We report on an 84-year-old woman with anteroseptal acute myocardial infarction. Emergency coronary angiography revealed the occlusion of proximal left anterior descending artery without collateral circulation, and percutaneous coronary intervention was performed. Two drug eluting stents were implanted, and the procedure was concluded with thrombolysis in myocardial infarction grade 3 without complications. Postoperatively, no murmur was audible on auscultation and no shunt flow was observed on transthoracic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Exclusion criteria: (1) Other types of myocardial infarction; (2) Sudden cardiac arrest or pulseless electrical activity may have ventricular septal defect; (3) Infective endocarditis, neoplasms in the heart, or other infections (4) Combined with hemorrhagic disease and thrombocytopenia; (5) Combined with obvious liver and kidney dysfunction; (6) Heart insufficiency, intolerance of surgery; (7) Severe valvular disease requires surgical treatment; (8) The survival period of other malignant diseases is less than 6 months.…”
Section: Research Objects and Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria: (1) Other types of myocardial infarction; (2) Sudden cardiac arrest or pulseless electrical activity may have ventricular septal defect; (3) Infective endocarditis, neoplasms in the heart, or other infections (4) Combined with hemorrhagic disease and thrombocytopenia; (5) Combined with obvious liver and kidney dysfunction; (6) Heart insufficiency, intolerance of surgery; (7) Severe valvular disease requires surgical treatment; (8) The survival period of other malignant diseases is less than 6 months.…”
Section: Research Objects and Groupsmentioning
confidence: 99%
“…Unfortunately, despite the decrease in incidence, the mortality (41-80%) and prognosis of such patients are still poor [1,5,6]. Studies have confirmed that elderly women, anterior myocardial infarction without collateral circulation are risk factors for ventricular septal rupture after acute myocardial infarction [7,8]. Basic research shows that matrix metalloproteinases and inflammatory cytokines play an important role in patients with ventricular septal rupture after myocardial infarction [9,10].…”
Section: Introductionmentioning
confidence: 99%